Perbandingan Mutu Tablet Ibuprofen Generik Dan Merek Dagang - Maria Dona Octavia; Fitriani Fitriani; Firmansyah Firmansyah (STIFARM Padang, 2011)
Ibuprofen is a non Steroid Anti-Inflamation Drug (NSAID) and most of Ibuprofen Tablets have been sold with generics name and branded name. This study is done to compare quality of Ibuprofen tablets 400 mg, there were 6 brands of tablet which they had consisted 3 brands of generic tablets and 3 brands of branded name tablets. Determination of quality Ibuprofen tablets could be showed from standard quality of Ibuprofen tablets were based at Farmakope Indonesia and USP. Quality parameter of Ibuprofen tablets included physical tablet evaluation, assay and dissolution profile test. Dissolution profile testing of Ibuprofen tablets was performed by paddle method and measured by Spectrofotometer UV used pH 7.2 phosphate buffer as medium. Assay of tablet was performed by Spectrofotometer UV in NaOH 0.1 N as medium. The test resulted that quality of Ibuprofen generic and branded tablets were same and fulfilled standard quality of Farmakope Indonesia and USP.